Artifcial Intelligence and Humanitarian Assistance: Reassessing the Role of State Consent - Maruša T. Veber (Zbornik Znanstvenih Razprav)
The author analyses the notion of State consent in the delivery of humanitarian assistance supported by artificial intelligence (AI) systems from the perspective of the existing applicable international legal regimes, in particular, the general legal regime of humanitarian assistance and the specific rules deriving from international humanitarian law and international human rights law. She argues that the notion of consent lies at the heart of these rules with a distinction made between strategic and operational consent to humanitarian assistance. The former refers to a State’s general consent to the delivery of humanitarian assistance on its territory, while the latter refers to the consent required at the operational level for the delivery of a particular type of humanitarian assistance in a specific geographically defined area. It is argued that valid reasons for withholding operational consent to AI-supported humanitarian assistance under international humanitarian law must be distinguished from the arbitrary withholding of strategic consent. While withholding operational consent may be legally justified, the arbitrary withholding of strategic consent to humanitarian assistance is prohibited under the relevant international legal regimes when it amounts to a violation of other existing obligations of the State concerned (e.g., under international humanitarian law or human rights law). In such situations the non-consensual delivery of humanitarian assistance could be legally justified either through United Nations Security Council authorisation or by secondary rules of international law, in particular countermeasures.